A comparative analysis of demographic and aetiological features in young and old patients of buccal mucosa cancer - Dr. Kalaivani Amitkumar; Dr. Ramasamy Padma; Dr. Prabhu Bhoopathy; Dr. Sivapatham Sundaresan; Dr. Vaishali Valluru (Tropical Journal of Pathology and Microbiology, 2019)
Background: Oral squamous cell carcinoma (OSCC) most commonly occurs in the middle-aged and older individuals. It is believed thatrole of aetiologyisdifferent in young and old patients. Objective: This study was conducted to analyse the comparisonof demographic and aetiological difference in young and old patients of buccal mucosa cancer. Materials and Methods: In this retrospective study, demographicand aetiological details were retrieved form medical records between Mar. 2013 and Jan. 2016. Results: The patients were grouped as younger (<40 years) and elder (aged 40 years and above). Of 198 patients, higherincidence was observed in older patients. Both younger and older groups showed male predominance (male: female ratio was 4:1 and 3.7:1 in younger and older groups, respectively). Conclusion: The present study proved that young (<40 yrs) adults with OSCC showed aggressive course compared with elders (≥40 yrs).The aggressiveness of disease may be due to the presence ofrisk habits. However, further studies need to find the hidden risk factors for lower survival.